Preconception Obstetrics and Rheumatology Consultation: A Protective Factor Against Spontaneous Abortion in Women With Autoimmune Rheumatic Disorders. Issue 1 (15th December 2020) - Javinani, Ali; Radmard, Fatemeh; Razavinia, Fatemeh Sadat; Masoumi, Maryam
Abstract : Supplemental digital content is available in the text. Abstract : Background: Autoimmune rheumatic disorders are a group of illnesses that significantly affect pregnancy outcomes. Aim: The aim of this study was to evaluate the incidence and risk factors of spontaneous abortion and its association with maternal medical care in women with autoimmune rheumatic diseases. Methods: In this medical record review study, we recruited patients who were referred to our clinic from September 2014 to September 2019. All confirmed pregnancies (based on a positive pregnancy test and sonogram) were included. Binary logistic regression was applied to construct the statistical model. Findings: The present study involved 97 women (215 total confirmed pregnancies) who were diagnosed with 7 different autoimmune rheumatic disorders. The rate of spontaneous abortion was 28.8%. In the univariate analysis, the preconception obstetrics and rheumatology consultation were negatively associated with spontaneous abortion ( p < 0.001; odds ratio [OR], 0.255; 95% confidence interval [CI], 0.136–0.480; and p < 0.001; OR, 0.042; 95% CI, 0.015–0.122, respectively). Perinatal obstetric care had a significant protective effect ( p < 0.001; OR, 0.260; 95% CI, 0.139–0.486). The multivariate analysis showed that the preconception rheumatology consultation ( p = 0.003; OR, 0.062; 95% CI, 0.010–0.393) was negatively associated with spontaneous abortions. The presence of active diseases before pregnancy ( p = 0.005; OR, 9.978; 95% CI, 2.023–49.223), anti-SSA/Ro ( p < 0.001; OR, 22.927; 95% CI, 4.921–106.818), and anticardiolipin IgM ( p = 0.004; OR, 298.207; 95% CI, 6.209–14, 323.037) were associated with a heightened risk of spontaneous abortion. Conclusions: A collaborative work carried out by maternal-fetal medicine specialists and rheumatologists could remarkably improve pregnancy outcomes.